The role of interleukin-8 in the immunopathogenesis of HIV-1 disease and tuberculosis - Meddows-Taylor, Stephen (My University, 2014)
Interleukin-8 (IL-8), a member of the C-X-C chemokine subfamily, is an important chemoattractant and cellular activator. This study was conducted to determine the role of IL-8 in the immunopathogenesis of HIV-I disease and tuberculosis. The first section involved determining the effect of infection with HIV-1, Mycobacterium tuberculosis and co-infection with both of these organisms on IL-8 j_ roduction in vivo. This was monitored by the determination of levels of serum or plasma EL-8 and peripheral cell-associated IL-8, assessing peripheral mononuclear (PBMC) and polymorphonuclear (PMN) cell capacity to produce IL-8 spontaneously or in response to various stimuli, and the detection of constitutive IL-8 mKNA expression in purified subsets of mononuclear cells. Results show that whereas there is evidence of detectable levels of cell-associated EL-8 (mKNA and protein) in peripheral cells of healthy individuals, this is largely lost in the disease states studied. Coupled with this was significantly increased circulating levels of EL-8 in serum and plasma found in HIV-1 infected individuals with or without concomitant pulmonary TB. On the other hand, the capacity of PBMC to produce IL-8 spontaneously ex vivo was enhanced in HIV-1 and TB patients and many of the HFV/TB group, but their corresponding capacities to respond to various stimuli was significantly diminished when compared to that of the normal donors. The release of IL-8 from PMN in the presence of an agonist was diminished mainly in individuals with pulmonary TB, which was further exacerbated by the presence of HIV-1 infection. HIV-1-infected individuals have an increased incidence of bacterial infections which could be related to defective functioning of PMN. The second section was aimed at detecting PMN abnormalities in HIV and I-HV/TB patients by monitoring EL-8-induced p-glucuronidase release and PMN chemotaxis in response to IL-8. IL-8-induced (I-glucuronidase release from PMN of normal individuals and TB patients occurred in a dose-dependent manner. In contrast, PMN from HTV-1 infected individuals, whether co-infected with M tuberculosis or not, showed a reciprocal response in that increasing IL-8 concentrations resulted in decreased enzyme release. This reciprocal slope of the IL-8 dose-response curve was altered for the majority of HIV-1 positive individuals tested irrespective of their CD4+ cell counts. In addition, PMN chemotaxis in response to IL-8 was also found to be significantly impaired in a group of HIV-1 infected patients coinfected w ithM tuberculosis when compared to healthy individuals. The third section of the study involved analysing the expression of the PMN cell surface markers, FcyRIII (CD 16), and the two human IL-8 receptors, designated IL -8RA and 1L-8RB. FcyRIII (CD 16) expression on the surface of PMN was significantly reduced in HIV-1 seropositive patients with pulmonary tuberculosis when compared to those individuals with either disease alone or healthy blood donors. A significant reduction in the percentage of PMN expressing IL-8RA and IL-8RB and in their respective fluorescence intensities was found in TB, HIV, and HTV/TB groups when compared to that obtained for the ND group. IL-8RA intensity of fluorescence was significantly decreased in the HTV/TB group when compared to the TB and HIV groups indicating a further down-regulation of IL-8RA expression owing to dual infection. On the other hand, IL-8RB fluorescence intensity was substantially reduced on PMN from patients with pulmonary TB and to a greater degree in those patients co-infected with HIV-1 and M. tuberculosis. Having found a reduction in the expression of both IL-8 receptors on PMN in all the infection groups, cellular events following the binding of IL-8 to IL-8 receptors on PMN isolated from dually infected patients, the group which showed the greatest reduction in IL-8 expression was analysed. Results indicated that the impairment of DL-8-dependent PMN functions such as degranulation and chemotaxis was associated with the reduced expression of IL-8 receptors on these cells. Increased circulating levels of IL-8 in HIV-1 infection and a diminished cellular capacity to produce IL-8 as shown in this study may have important implications for antimicrobial defences and normal immune processes. A dysregulated production of IL-8 in vivo is likely to play a role in the pathogenesis of HIV-1 disease, pulmonary tuberculosis, and dual infections with both organisms. In addition, cellular responses dependent on specific receptor engagement and the subsequent translation of signal transducing events that lead to phagocyte effector functions are clearly impaired in IL-8 receptor deficient phagocytes. Abnormal PMN functioning in HTV-1 infected individuals, as shown here by defective degranulation and chemotactic responses, have important implications in the pathogenesis of HIV-1 infection in terms of their ability to clear secondary microbial infections. Future attempts should be aimed at defining the mechanisms that bring about these changes in order to contribute to a greater understanding of the mechanisms that lead to an enhanced risk of superinfections in immunosuppressed individuals.
Keywords: Immunity, Cellular; Interleukin-8--immunology